Freight Trains - Arnold, Quinn M. (Mankato, Minnesota : Creative Education and Creative Paperbacks, 2020)
A kindergarten-level introduction to freight trains, covering their drivers, role in transportation, and such defining features as their locomotives.
t Long line of cars -- t Conducting the train -- t Picture a freight train.
Includes bibliographical references and index
Keywords: Railroad trains -- Juvenile literature; Railroad trains; Juvenile works; Juvenile literature